Factors affecting auditors' independence in Singapore - Chan, San San (2008)
This research studied the factors affecting auditors' independence from two perspectives; the audit firm as a single economic entity and the individual auditors. Several factors such as the client's ability to negotiate audit fee were found to affect auditors' independence aversely while factors such as the provision of specialised management advisory services affect independence positively.